فقه الحديث عند الإمام ابن حزم رحمه الله وأثره في تأصيل منهجه الأصولي: دراسة تحليلية في ضوء كتبه: The Jurisprudence of Hadith According to Ibn Hazm and Its Impact on the Foundations of His Usūl Methodology: An Analytical Study in Light of His Works - Fawad Ali; Dr. Iqrar Hussain (Al Manhal Research Journal, 2025)
This study examines the jurisprudence of Hadith (Fiqh al-Ḥadīth) according to Imām Ibn Ḥazm (d. 456 AH) and its significant role in shaping his uṣūl al-fiqh methodology. Employing an analytical approach grounded in his principal works, the article demonstrates how his strict adherence to textual evidence informed both his legal reasoning and theoretical framework. The study is structured in two parts. The first outlines the foundational principles of his methodology, including the Qur’an, the authentic Sunnah, consensus (ijmāʿ), definitive textual inference (dalīl), the principle of continuity (istiṣḥāb), and the presumption of permissibility (ibāḥah) in the absence of explicit revelation. These sources collectively reflect his commitment to certainty, authenticity, and direct reliance on revealed texts. The second part explores the principles he rejected, such as analogical reasoning (qiyās), juristic preference (istiḥsān), unrestricted public interest (maṣāliḥ mursalah), blocking the means (sadd al-dharāʾiʿ), and the authority of a Companion’s opinion. It also addresses his position on previous religious laws and the practice of the people of Madinah. The study concludes that Ibn Ḥazm’s Fiqh al-Ḥadīth is foundational, representing a coherent, text-centered legal methodology within Islamic jurisprudence.